Continuous polydimethylsiloxane filament fabrication and characterizations - Quentin Watel; Aurélie Cayla; Fabien Salaün; François Boussu (eXPRESS Polymer Letters)
In this work, a PDMS spinning technique is developed and enables the continuous production of a filament with a circular cross-section (~500 μm diameter). The production of continuous silicone polymer filaments can be useful in the textile field to provide new properties in applications such as weaving, knitting or composite reinforcement. The method involves injecting the pre-polymer and curing agent mixture into a heated oil bath (202–215 °C) to simultaneously shape and cure the PDMS. The morphological and mechanical properties of the filament are studied regarding the production parameters (formulation, needle diameter, bath temperature, conveyor belt speed). The most homogeneous filament is produced at the highest temperature (215°C) and conveyor belt speed (13.6 m∙min–1). When subjected to cyclic mechanical stress, the PDMS filament produced exhibits stable mechanical behavior, making it suitable for a wide range of applications.